Clan Culture Implementation at Sang Hyang Seri With the Improvement Evaluation Method - SURYANI, Yosi; CLAUDIA, Cindy; WIRDA, Fisla; GUSTIAWAN, Wilson; YOYET, Eva; JUMYETTI, Jumyetti (PT Keberlanjutan Strategis Indonesia, 2024)
In order to ensure the continuity and progress of the company, leaders are required to be able to carry out various special management of employees. One way is to pay attention to the application of culture in the organizational environment. The purpose of this study is to review the position of implementing the clan culture used by PT Sang Hyang Seri and provide recommendations for improving the applied clan culture. The method of this research is evaluative research. The data used in this study came from questionnaires and direct observation of the research object. Based on the results of the assessment using the Likert scale method, it can be seen the position of each element of organizational culture. The results of the study show that there are three elements of culture that are in a